Conservative Management of Spinal Tuberculosis: Initial Series from Pakistan - Abbas, Asad; Rizvi, Syed Raza Haider; Mahesri, Mufaddal; Salahuddin, Hisham Raza Aleem (Korean Society of Spine Surgery, 2013)
STUDY DESIGN: A prospective study on spinal tuberculosis (TB) at a tertiary care hospital in an endemic region. PURPOSE: The aim of the study is to reiterate the importance of conservative management of spinal TB. OVERVIEW OF LITERATURE: Spinal tuberculosis can present with wide spectrum of symptoms, with back pain being the most common symptom. It is the leading cause of non-traumatic paraplegia in developing countries. There is an emerging trend to operate on patients early with spinal TB. METHODS: Forty-seven (M=14, F=33) patients were enrolled in the study during the four year study period. Initially, all the patients were subjected to computed tomography guided percutaneous needle aspiration (PCNA) followed by antituberculous therapy (ATT) for 12 months. Indications for surgery included patients with moderate to severe symptoms in which PCNA either failed, was impossible to carry out, or produced minimal improvement within 48 hours. RESULTS: Presenting complaints included pain (95.7%), weakness (85.1%) and sphincter involvement (12.8%). On the magnetic resonance imaging, a paravertebral abscess was seen in 37 (78.7%), disc and body destruction in 29 (61.7%), and an epidural abscess in 12 (25.9%) patients. Of the 47 patients, 9 (19.1%) required surgery, 4 of whom had failed PCNA attempts and 5 demonstrated indications despite successful PCNA. CONCLUSIONS: The results of conservative treatment consisting of PCNA and ATT for at least 12 months in compliant patients are excellent. A combined approach using clinical staging, PCNA, and ATT can minimize surgical intervention in most patients. However, ATT remains to be the cornerstone of management of spinal TB.